NATIONAL INTEGRATION AND DEMOCRATIZATION PROCESS IN NIGERIA - ADAMU, Abdulrahman; ETILA, Shaibu Moses (Socialscientia: Journal of Social Sciences and Humanities, 2019)
This paper interrogates the problematic of national integration confronting contemporary Nigeria which is regarded as an indelible mark of unity of purpose. No doubt, the issue has attracted diverse interests from various parts of the country, and generated robust and scholarly debates essentially among the social scientists on how to curb the challenges that it is posing to the country’s democratization process. Methodologically, this paper relies heavily on the secondary sources of data and descriptive analysis. It reveals that the major contending issues serving as anathema to national integration in Nigeria include the manipulation of religion by both political and religious leaders, the continuous agitation for resource control, lack of trust among the various ethnic groups which had led to ethno-religious and political conflicts in Nigeria, revenue sharing formula, complains of domination and marginalization cum minority/majority syndrome, activities of the various militia groups from all parts of the country, the common practice of bribery and corruption which has eaten deep into the fabrics of the Nigerian society and a host of others. The paper recommends among others that there is the need to convey a truthful and genuine sovereign national/constitutional conference that would offer the Nigerian people the opportunity to discuss the various challenges confronting the nation. It is expected that the conference would offer the country a brand new constitution that would favour the general populace as against what we have today as a constitution of the ruling class.